Lifelong learning: conceptualizations in european educational policy documents - Alves, Mariana G. (2019)
Over recent years, lifelong learning has been a central and guiding principle in the formulation of European educational policies. Within this general framework, the authors have been developing a research project that allows them to approach the theme of lifelong learning and European educational policies, taking into account four levels of analysis, namely: the supranational, the national, the institutional and, finally, the individual level of analysis. This methodological strategy reflects a theoretical understanding of policy as the result of the actions of a diversity of actors at different levels. This article focuses on the supranational level of analysis, drawing on data from an analysis of European educational policy documents. First, the authors clarify the methodological issues raised by the research findings presented. Second, they discuss the results concerning the process of definition of European educational policies. Third, the authors briefly revisit the evolution of the idea of lifelong learning and discuss the results regarding its plurality of meanings and conceptualizations within the documents considered for analysis.